Exploring Opportunities and Challenges in E-Health Adoption in Libya - Elfituri, Emad (Université d'Ottawa / University of Ottawa, 2025)
The aim of this mixed method study was to explore the opportunities and challenges facing e-health adoption in Libya, and to uncover strategies to facilitate the adoption of this technology by studying four health institutions and obtaining the insider expertise of service providers. Using a case study approach, this study aimed to understand the opportunities and challenges facing the adoption of health information technology, with an emphasis on electronic health records, in these institutions. The data collection methods consisted of 16 in-depth interviews, 160 individual questionnaire sheets, and official documentation related to the Libyan health sector. The research was guided by the unified theory of acceptance and use of technology to help explain service providers' behaviour regarding the use of health information technology. The general findings uncovered the following six themes: (1) critical issues related to vulnerabilities in technological infrastructure, (2) cybersecurity-related risks, (3) resistance to change, (4) training and awareness problems of healthcare professionals, (5) financial constraints, and (6) the absence of a comprehensive legal framework. Meanwhile, advanced analytics found that successful adoption of eHealth solutions in Libya could significantly improve healthcare delivery, reduce medical errors, enhance economic efficiency, and improve patient care. The study contributes valuable research knowledge by identifying challenges and strategies that could help in the successful implementation of electronic health records. The results suggest the need for future economic research to address workforce issues in order to improve the overall quality of health services, as well as point the way to other relevant topics for future study.
Keywords: e-health solution; EHRs; opportunities; challenges; Libyan health sector; technology acceptance model